Axial prevascularization of porous matrices using an arteriovenous loop promotes survival and differentiation of transplanted autologous osteoblasts. - Arkudas, Andreas; Beier, Justus P.; Heidner, Kristina; Tjiawi, Jimmy; Polykandriotis, Elias; Srour, Safwan; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Tissue Engineering -Larchmont, 2007)
Generation of axially vascularized bioartificial bone might be performed using matrix neovascularization in connection with osteoblast injection. We sought to evaluate whether prevascularization of porous hard matrices using an arteriovenous (AV) loop promotes survival of transplanted osteoblasts. A processed bovine cancellous bone matrix was inserted into the AV loop. Six weeks later, 5 x 10(6) carboxyfluorescein diacetate-stained osteoblasts were injected into the matrix (group A, n = 34). Osteoblast-seeded matrices without prevascularization were implanted subcutaneously as controls (group B, n = 32). Specimens were subjected to histologic, morphometric, and molecular-biological analysis after 1, 4, 8, and 16 weeks. Upon cell injection, matrices were completely vascularized. An intense foreign body reaction was observed in matrices from both groups. Group A was significantly superior to group B in terms of osteoblast survival at any time point. Expression of bone-specific genes was detected in the AV loop group but not in the subcutaneous control. Bone formation was only detectable in 1 long-term animal of group A. This study demonstrates for the first time that axial prevascularization increases the survival of implanted osteoblasts in porous matrices. Matrices with optimized biocompatibility might eventually facilitate generation of axially vascularized bone tissue after injection of osteogenic cells in the AV loop model.